Toward FGF2 reduction in cultured meat media: polyphenol salts enhance growth and differentiation of bESC aggregates - Savyon, Gaya; Korol, Ruchama; Abdel-Haq, Muhammad; Saadon, Sara Ben; Bistritz, Dana; Lankry, Hodaya; Peled, Yuval; Rak, Roni; Levavi-Sivan, Berta; Benny, Ofra; Domb, Abraham J.; Nachman, Iftach (Frontiers in Nutrition, 2025)
Recombinant growth factors, particularly fibroblast growth factor 2 (FGF2), are major cost drivers in the production of cultured meat. In this study, we investigated the potential of polyphenol salts to reduce reliance on FGF2 in media supporting the proliferation and mesodermal differentiation of bovine embryonic stem cell (bESC) aggregates. The activation potential of these salts was first verified using a luciferase reporter assay in COS-7 cells expressing human FGFR1. Several compounds, particularly Na-Quercetin, induced strong, dose-dependent FGFR1 activation with sub-nanomolar EC₅₀ values, comparable to FGF2. We then evaluated the use of three of the salts Sodium-Curcumin (NaCur), Potassium-Naringenin (K-Ng) and Sodium-Quercetin (Na-Q) on bESC aggregates. NaCur significantly enhanced aggregate growth under reduced FGF2 conditions, restoring proliferation to levels exceeding those observed with 20 ng/mL FGF2 alone. Additionally, NaCur supported mesodermal differentiation, as indicated by Brachyury expression, when combined with low-dose FGF2. K-Ng and Na-Q improved aggregate growth in the absence of FGF2 serum-free conditions but were insufficient to support mesodermal differentiation. These findings suggest that NaCur can reduce the required concentration of recombinant FGF2 while supporting both proliferation and differentiation, whereas K-Ng and Na-Q may be better suited for the early expansion phase. Our results highlight the potential of using polyphenol supplementation as a strategy to lower medium costs in cultured meat production systems.